Global and International Logistics - Shibasaki, Ryuichi; Watanabe, Daisuke; Kawasaki, Tomoya (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book contains 10 reviewed papers published as a Special Issue "Global and International Logistics" in the journal Sustainability, edited by Prof. Dr. Ryuichi Shibasaki, Prof. Dr. Daisuke Watanabe, and Dr. Tomoya Kawasaki. The topics of the papers contain the impact of logistics development under the China's Belt and Road initiative (BRI) by using the improved gravity model, strategies against barriers to the BRI from a logistics and supply chain management perspective, the dynamic interaction between international logistics, and cross-border e-commerce trade, the effect of China's restrictive programs on the international trade of waste products, the empty container repositioning problem of shipping companies with foldable containers, port capacity and connectivity improvement in the hub and feeder network in Indonesia, GHG emission scenarios for the maritime shipping sector using system dynamics, incorporating a shipping and shipbuilding market model, the emission inventory and bunker consumption from a LNG fleet from an automatic identification system database, the factors that can help select between land transport and maritime shipping in long-distance inter-regional cross-border transport, and container transport simulations in Myanmar with the global logistics intermodal network assignment model including both maritime shipping and land transport in the land-based Southeast Asia region. Some papers are related to the 8th International Conference on Transportation and Logistics (T-LOG 2020) which was held online on 6-7 September 2020 hosted by Universitas Internasional Semen Indonesia.